Testing the relationship between testate amoeba community composition and environmental variables in a coastal tropical peatland. (August 2018) - Swindles, Graeme T.; Baird, Andy J.; Kilbride, Elliot; Low, Rob; Lopez, Omar
Highlights: We examined the ecology of testate amoebae (TA) in a tropical peatland. Hydrological variation is the strongest control on TA distribution. TA probably have limited potential as sea-level indicators in tropical wetlands. The new dataset was used to test an existing transfer function from Amazonia. Abstract: We investigated the ecology of testate amoebae (TA) in a coastal tropical peatland to evaluate their potential as environmental indicators in these ecosystems. At 10 positions in five locations in a transect running into the peatland away from the coast, we measured pore-water pH, pore-water electrical conductivity, soil moisture content (MC), and water-table depth (WTD). The WTD data were collected using dipwells fitted with self-recording pressure transducers that logged at 10-min intervals over a 25-day period. Multivariate statistical analysis showed that hydrological metrics (WTD and MC) were the strongest environmental controls on TA ( p < 0.001) in this site, corroborating the single previous study from western Amazonia. Changes in pH and electrical conductivity, reflecting marine influence, were also significant, but less so ( p < 0.05; p < 0.01 respectively). Transfer functions for WTD and MC were developed using weighted averaging partial least-squares regression, and were found to perform well under 'leave-one-out' cross validation ( R 2 = 0.80, RMSEP = 4.64 cm; R 2 = 0.89; RMSEP = 1.57 cm). Our results clarify the autecology of several taxa found in tropical peatlands. Centropyxis aculeata is an unambiguous indicator of surface water, Hyalosphenia subflava "minor" (<60 μm length) is a dry indicator, whereas Hyalosphenia subflava "major" (>60 μm length) lives in wetter conditions. The difference in habitat preference of the two forms of Hyalosphenia subflava suggests that this taxon is most probably a species complex. We use the new high-quality dataset to test an existing transfer function from western Amazonia: the results show that the previous model has good predictive power for reconstructing past WTDs in tropical peatlands ( r = 0.87; p < 0.005). The reconstruction of sea-level change from tropical coastal wetlands may prove problematic because the key indicators of marine influence, reflected in pH and electrical conductivity, are taxa with weak idiosomic tests that do not preserve readily in the peat archive (e.g. Tracheleuglypha dentata, Trinema lineare ). Our work shows the potential of using high-quality hydrological measurements for increasing the precision of transfer function models.